A paisagem e a geodiversidade: uma proposta de classificação e divulgação do valor patrimonial - Soares, Jefferson Paulo Ribeiro (2021)
The Geodiversity represents the abiotic characteristics of the Earth. In addition to being responsible for characterizing the physical aspects of the terrestrial globe, geodiversity in interaction with biodiversity forms the wide variety of landscapes that exist on the terrestrial globe, and such interaction resembles a symbiosis and is crucial for maintenance and quality of life in the Earth. Sometimes, some elements of geodiversity have characteristics that distinguish them and distinguish them from the others, such as rare rock formations, which show ancient processes of the formation and dynamics of the earth's crust or the evolution of life, or even those which are shelter for inscriptions that evidence records of human cultural expression. In view of the uniqueness of these areas, it is necessary to classify them and measure their value. Thus, the thesis work has as main objective to propose a methodology for the classification of geomorphological heritage in order to make the disclosure of the measured patrimonial value more accessible to the general public. To this end, the geosites present in the Milton Brandão City were used as the application area, and this choice was motivated by the fact that there are geomorphological formations in this area with potential heritage value not yet measured. In order to fulfill the proposed objective, a method of inventorying, quantification and classification of assets was developed, based mainly on the proposal of Brilha (2005) and which resulted in the elaboration of parameters of asset classification ranging from the letter “A”, for the maximum equity value, to the letter “G”, for those with minimum value. The application of this methodology in the research area resulted in the classification of six geosites evaluated with grade “D”, one rated as grade “F” and one rated as grade “C”. The work concludes that it is possible to build a methodology for asset classification that results in a simple and easy to understand serialization, especially through a form of presentation with which people are already relatively familiar. In addition, one of the recommendations of the methodology developed is that, for geosites that obtained a classification up to the letter “D”, actions to disseminate the equity value, such as information panels, were carried out. Therefore, seven of the eight inventoried geosites that obtained a classification between “A” and “D” - Alto of the Morais, Nogueira’s Waterfall, Santo Antônio’s Waterfall, São Gonçalo’s Viewpoint, Montain Range of the Cruzeiro, Montain Range of Two Holes and Montain Range of the Bat dissemination proposals made in the form of information panels. Thus, the methodology developed proved to be valid for carrying out the classification and disclosure of the equity value of areas of relevant geomorphological interest.